2003
DOI: 10.1126/science.1079707
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evolution of Egg Size in Captive Salmon

Abstract: Captive breeding and release programs, widely used to supplement populations of declining species, minimize juvenile mortality to achieve rapid population growth. However, raising animals in benign environments may promote traits that are adaptive in captivity but maladaptive in nature. In chinook salmon, hatchery rearing relaxes natural selection favoring large eggs, allowing fecundity selection to drive exceptionally rapid evolution of small eggs. Trends toward small eggs are also evident in natural populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
252
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 264 publications
(262 citation statements)
references
References 27 publications
8
252
2
Order By: Relevance
“…Previous work has suggested that growth rate may be under strong selection in hatcheries because steelhead are released as yearling smolts, whereas fish in the wild generally take 2 y or longer to smolt (22). Other possible contenders for selected traits include egg size, fecundity, physiological processes associated with smoltification, and individual behaviors (e.g., predator avoidance) (10,(22)(23)(24). For the F1 runyear in which selection was not detected (1995), the smolts were reared in low-density conditions and the release size of the smolts was considerably larger than in other years (Table S3), which points to crowding as a possible selection pressure (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has suggested that growth rate may be under strong selection in hatcheries because steelhead are released as yearling smolts, whereas fish in the wild generally take 2 y or longer to smolt (22). Other possible contenders for selected traits include egg size, fecundity, physiological processes associated with smoltification, and individual behaviors (e.g., predator avoidance) (10,(22)(23)(24). For the F1 runyear in which selection was not detected (1995), the smolts were reared in low-density conditions and the release size of the smolts was considerably larger than in other years (Table S3), which points to crowding as a possible selection pressure (25).…”
Section: Discussionmentioning
confidence: 99%
“…When maternal effects are themselves heritable, populations can still respond to natural selection via indirect genetic effects [9]. Indeed, in a captive population of chinook salmon, a mother-daughter regression revealed egg mass to be highly heritable, indicative of a genetic basis for egg provisioning [32].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, captive bred animals often have reduced fitness when reintroduced to natural conditions (5). Selective pressures disrupted by captivity include inbreeding avoidance, effective population size, disease exposure, predation, and sexual selection.…”
mentioning
confidence: 99%